2023
DOI: 10.1146/annurev-psych-021422-041757
|View full text |Cite
|
Sign up to set email alerts
|

Turning Attention Inside Out: How Working Memory Serves Behavior

Abstract: Flexible behavior requires guidance not only by sensations that are available immediately but also by relevant mental contents carried forward through working memory. Therefore, selective-attention functions that modulate the contents of working memory to guide behavior (inside-out) are just as important as those operating on sensory signals to generate internal contents (outside-in). We review the burgeoning literature on selective attention in the inside-out direction and underscore its functional, flexible,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
108
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(120 citation statements)
references
References 160 publications
11
108
1
Order By: Relevance
“…Instead, we found that the selection of task-relevant internal representations was delayed when endogenous and exogenous selection mechanisms were placed in conflict compared to when they were aligned. This finding supports claims that the selection of external sensory inputs and internal memory representations are mediated by different mechanisms (Chun et al, 2011; van Ede & Nobe, 2022).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Instead, we found that the selection of task-relevant internal representations was delayed when endogenous and exogenous selection mechanisms were placed in conflict compared to when they were aligned. This finding supports claims that the selection of external sensory inputs and internal memory representations are mediated by different mechanisms (Chun et al, 2011; van Ede & Nobe, 2022).…”
Section: Discussionsupporting
confidence: 89%
“…External attention is directed to sensory inputs, and competition between endogenous and exogenous factors sometimes results in attention “capture” by unexpected, salient, and valuable but otherwise task-irrelevant stimuli (Theeuwes, 1992; Folk et al, 1992; Bacon & Egeth, 1994; Folk et al, 2009; Fukuda & Vogel, 2009; Anderson et al, 2011). Endogenous and exogenous factors also compete to control the selection of internal representations (e.g., van Ede et al, 2020; van Ede & Nobre, 2022), but this competition is resolved in a fundamentally different way. We observed no evidence for the selection of salient internal representations akin to capture effects seen in external attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flexible behaviors require dynamic sensory inputs to be compared with internal representations of beliefs and goals. Many of these comparisons are mediate by working memory (WM), which stores representations of sensory phenomena and possible actions (3, 17). There is growing appreciation that WM encodes representations of multiple prospectively relevant stimuli and responses to maximize behavioral flexibility (3).…”
Section: Discussionmentioning
confidence: 99%
“…Many of these comparisons are mediate by working memory (WM), which stores representations of sensory phenomena and possible actions (3, 17). There is growing appreciation that WM encodes representations of multiple prospectively relevant stimuli and responses to maximize behavioral flexibility (3). Thus, mechanisms are needed to select WM content that is most relevant for immediate behaviors.…”
Section: Discussionmentioning
confidence: 99%